Road damage caused by heavy duty vehicles. (4th August 2014) - Goktan, A.; Mitschke, M.
This paper reviews some research carried out on road damage caused by heavy vehicles. Based on US AASHO tests, the research looks at vehicle specifications such as load and axle positions, and road parameters such as thickness and type. Lateral load and longitudinal tyre forces are also considered. The paper concludes by listing a number of design precautions that could be taken to minimize damage, including the use of large–volume tyres with reduced air pressures instead of conventional twin wheels.